PENGARUH HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PADA RESTORAN KEBULI JORDAN BEKASI - Cornelia Dumarya Manik; Ridho Muhammad Elsa Anugrah (Journal of Research and Publication Innovation, 2025)
This research aims to determine the effect of price and promotion on purchasing decisions at the Kebuli Jordan restaurant in Bekasi. The research method used is causal associative with a quantitative approach and assisted by data processing with the SPSS version 26 application. The population at the Kebuli Jordan restaurant is 16,417 consumers. The sample for this research was determined using the Slovin formula as many as 99 respondents. Data analysis techniques use simple linear regression tests, multiple linear regression tests, correlation coefficient tests, coefficient of determination tests and hypothesis tests. The research results show that price has a positive and significant influence on purchasing decisions with a t-count value of 6.803 > t-table 1.984 and a sig. 0.000 < 0.05. Promotion has a positive and significant influence on consumer satisfaction with a t-value of 7.049 > t-table 1.984 and a sig value. 0.000 < 0.05. Price and Promotion simultaneously have a positive and significant influence on consumer satisfaction with the regression equation Y= 10.999 + 0.257 X1 + 0.416 X2. The coefficient of determination value is 38.6% while the remaining 61.4% is influenced by other factors. Hypothesis testing obtained an F-count value of 30.162 > t-table 3.091 and a sig value. 0.000 < 0.05.